Pengembangan Augmented Reality Sebagai Media Edukasi Pengetahuan Bencana Alam Gunung Berapi - Dian Nurdiana (Jurnal Manajemen Informatika (JAMIKA), 2020)
Indonesia is an archipelagic country in which there are many volcanoes, with 76 mountains declared active throughout the islands in Indonesia. Volcanic disasters occur almost every year and often cause many lives. One example is in 2018 the eruption of Mount Anak Krakatau which caused a tsunami resulting in 432 fatalities according to BNPB data. From these issues it is necessary to make an effort to educate the community on volcanic disaster knowledge so that they can reduce fatalities. Augmented reality is one of the media that is being warmly used, there are already many fields that utilize this media as an educational medium. The purpose of this study is how to develop applications for the education of Augmented reality-based volcanic natural disasters. The model used for its development uses the watelfall model, while the testing uses black box testing and the OS used to run this application is based on Android. The results of this study are to make an information media in the form of an Augmented reality-based mobile application for volcanic knowledge natural media, the media to be created is named "simerapi".